Anesthetic Management of a Parturient with PHACE Syndrome for Cesarean Delivery. Issue 10 (15th November 2015) - Martel, Colleen; Robertson, Richard; Williams, Frank B.; Moore, R. Clifton; Clark, Allison
Abstract : PHACE syndrome is a disorder that features p osterior fossa malformations, h emangiomas, a rterial anomalies, c oarctation of the aorta and cardiac defects, and e ye abnormalities. PHACE syndrome includes abnormalities in several organ systems that may influence anesthetic management. We discuss the anesthetic management of a 26-year-old woman with PHACE syndrome presenting for cesarean delivery. Management included careful airway examination, slowly dosed epidural anesthesia, close hemodynamic monitoring aided by a radial arterial line, and continuous intraoperative neurologic assessment.